Finite element-based simulation and analysis of dragline bucket in static and dynamic loading condition - Azam S.F.; Rai P. (My University, 2025)
Draglines are bulky and expensive machines widely utilized in opencast mines for overburden stripping. Due to tedious working conditions, a variety of fatigue failures in dragline components are common. Bucket is one of the main components of dragline, and it is a source of external load on the machinery than its interaction through broken rock material directly. Hence, dragline buckets are the most vulnerable components of wear, tear and related failures. This article analyses the von Mises stresses using the finite element method (FEM) under the static and dynamic loading conditions. In this study, the three-dimensional solid bucket models were developed in AUTO CAD and were investigated for stress, deformation, and safety factor on the dragline bucket under static and dynamic loading conditions using the ANSYS 18 software. FEM outcomes have been highlighted from teeth, the arc of anchors and hitch elements have a maximum value of stress and a minimum value of safety factor under various loading conditions. The purpose of this study was to prognosticate the bucket failure, the strength of bucket teeth and identify the sensitive areas of the dragline bucket. © 2019 Current Science Association, Bengaluru.